2016
DOI: 10.3892/etm.2016.3749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on local application of low-dose insulin for promoting wound healing after operation for deep burns

Abstract: Transplanted free skin flaps are often needed to treat deep burns; their survival, however, is less than optimal. This study examined whether local low-dose insulin injections can promote flap survival and wound healing after surgery. A total of 165 patients who underwent free skin flap transplantation for simple deep burns were enrolled in the study and divided into 5 groups of 33 patients each: Blank control group (no local subcutaneous drug injections), saline control group (saline injections), low-dose ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…20,21,23,25 This was due to the fifth study using a different parameter to explore the rate of healing-percentage at Days 7 and 14 instead of mm 2 /day. 26 Despite omission, the study showed a statistically significant difference favouring the insulin groups, where p < 0.001 at both Days 7 and 14. Table 3 displays the mean rate of healing for each study with the standard deviation and p-value.…”
Section: Patient Characteristicsmentioning
confidence: 89%
See 3 more Smart Citations
“…20,21,23,25 This was due to the fifth study using a different parameter to explore the rate of healing-percentage at Days 7 and 14 instead of mm 2 /day. 26 Despite omission, the study showed a statistically significant difference favouring the insulin groups, where p < 0.001 at both Days 7 and 14. Table 3 displays the mean rate of healing for each study with the standard deviation and p-value.…”
Section: Patient Characteristicsmentioning
confidence: 89%
“…The seven RCTs included in this review were published between August 2009 and November 2021. [20][21][22][23][24][25][26] These were undertaken in either of the following countries: China, Egypt, India or Iran. Four of the seven studies had a two-armed RCT design, where the therapeutic group explored insulin as a treatment for wound healing and the control group had a standard saline placebo.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…(124)(125)(126)(127) In the context of hypermetabolism secondary to severe burns, insulin seems to be an effective and safe anabolic agent for burn patients for several reasons: (1) it is less expensive than rhGH or IGF-1, (2) its side effect profile is well established and is limited primarily to hypoglycemia, (3) it seems to improve outcome by decreasing serum glucose levels and (4) it apparently enhances wound healing, both systemically and locally administered. (128)(129)(130)(131)(132) It is widely used in critically ill adult and pediatric patients that require glycemic control. From an anabolic perspective, the risk of causing hypoglycemia in a normoglycemic patient must be taken into consideration.…”
Section: Insulinmentioning
confidence: 99%